The Use of Dating Apps in Marital Relationships from An Islamic Family Psychology Perspective - Sholehah, deah; noviana, lia (Al-Syakhsiyyah: Journal of Law and Family Studies, 2025)
Basically this dating application is intended for people who are looking for a mate. So if a married couple becomes a dating application user, it can affect household life in forming a sakinah family. And of course, it can lead to conflicts that will occur in domestic life, which can have consequences on Family Psychology. This study aims to determine the influence and efforts to use dating applications on married couples in forming families sakinah perspective of Islamic Family Psychology. The type of research conducted by the author is qualitative research that uses qualitative methods of netnography. Netnography is a research conducted online, through observation and in-depth interviews using digital media in accordance with the research. The results of this study is the use of dating applications in married couples can have a bad influence on domestic relationships, including: causing a less open attitude that occurs in married couples, silent attitude when knowing their partner becomes a dating application user on the grounds that they do not want to fight with a partner, hindering in forming a sakinah family, and infidelity. Then it can be understood that the effect of using dating applications for married couples according to the Islamic family perspective is to make married couples rarely or even never take the time to discuss domestic life, there is no sense of responsibility between husband and wife to maintain family harmony, and away from religion that can plunge a person into bad deeds. While preventive efforts that can be done on married dating application users include: maintaining communication, maintaining family harmony, being open to each other, having the principle of deliberation, and forgiving each other. It can be understood that the preventive efforts that can be done on the dating application users in accordance with Islamic Family Psychology, namely: maintaining good communication, building a good understanding between married couples, suitability in creating a sense of security and comfort that exists in the domestic environment, and a sense of reciprocity between couples in self-openness.